Before platelets: the production of platelet-activating factor during growth and stress in a basal marine organism. Issue 1884 (15th August 2018) - Galtier d'Auriac, Ines; Quinn, Robert A.; Maughan, Heather; Nothias, Louis-Felix; Little, Mark; Kapono, Clifford A.; Cobian, Ana; Reyes, Brandon T.; Green, Kevin; Quistad, Steven D.; Leray, Matthieu; Smith, Jennifer E.; et al.
Abstract : Corals and humans represent two extremely disparate metazoan lineages and are therefore useful for comparative evolutionary studies. Two lipid-based molecules that are central to human immunity, platelet-activating factor (PAF) and Lyso-PAF were recently identified in scleractinian corals. To identify processes in corals that involve these molecules, PAF and Lyso-PAF biosynthesis was quantified in conditions known to stimulate PAF production in mammals (tissue growth and exposure to elevated levels of ultraviolet light) and in conditions unique to corals (competing with neighbouring colonies over benthic space). Similar to observations in mammals, PAF production was higher in regions of active tissue growth and increased when corals were exposed to elevated levels of ultraviolet light. PAF production also increased when corals were attacked by the stinging cells of a neighbouring colony, though only the attacked coral exhibited an increase in PAF. This reaction was observed in adjacent areas of the colony, indicating that this response is coordinated across multiple polyps including those not directly subject to the stress. PAF and Lyso-PAF are involved in coral stress responses that are both shared with mammals and unique to the ecology of cnidarians.